Judicial Modification of Contract as a Result of Decrease in Money Value - Ghafour Khoeini; Atiyeh shamsollahi; Soheil Zolfaghari (Faṣlnāmah-i Pizhūhish-i Huqūq-i Khuṣūṣī, 2013)
AbstractThe judicial modification of contract as a result of decrease of moneyvalue is a legal- economic concept emerged due to the economic fluctuationin recent century. According to the legal, philosophical and the economicbasics presented for modification and decreasing money value, unfairpossession seems to be a good basis, although the current legal systemhardly accepts it. It seems that the legislator has accepted the hardshipsresulting from decreasing value as a basis.Regarding its nature decrease in money value causes liability and it canbe compensated. The important point is possibility of maintaining thecontract at its own forms considering value decrease. So in some cases valuedecrease of money, modification will not be justifiable. Continuation of thecontract and keeping the agreed terms can be a suitable equivalent.